A single nanophotonic platform for producing circularly polarized white light from non-chiral emitters - Jose Mendoza-Carreño; Simone Bertucci; Mauro Garbarino; Matilde Cirignano; Sergio Fiorito; Paola Lova; Miquel Garriga; Maria Isabel Alonso; Francesco Di Stasio; Agustín Mihi (Nature Communications)
Abstract Direct manipulation of light spin-angular momentum is desired in optoelectronic applications such as, displays, telecommunications, or imaging. Generating polarized light from luminophores avoids using optical components that cause brightness losses and hamper on-chip integration of light sources. Endowing chirality to achiral emitters for direct generation of polarized light benefits from existing materials and can be achieved by chiral nanophotonics. However, most chiral nanostructures operate in narrow wavelength ranges and involve nanofabrication processes incompatible with high-throughput production. Here, a single nanophotonic architecture is designed to sustain chiroptical resonances along the visible spectrum. This platform, fabricated with scalable soft-nanoimprint lithography transfers its chirality to conventional emitters (CdSe/CdS nanoplatelets, CdSe/CdS quantum dots, CsPbBr3, CsPbI3 perovskite nanocrystals and F8BT) placed atop, achieving a high dissymmetry emission factor (g lum > 1). The dynamics study suggests enhanced out-coupling efficiency for one helicity by the photonic structure. Finally, a white light-emitting blend containing different emitters shows simultaneous dissymmetric emission values along the visible spectrum with this chiral nanophotonic platform.